Environment-friendly building material with long service life and preparation method thereof
By employing methods such as chemical crosslinking, in-situ composite, and reversible crosslinking, the problem of phase change material leakage during the hot pressing process of environmentally friendly building materials has been solved, maintaining the mechanical and antibacterial properties of the materials and achieving the preparation of long-life environmentally friendly building materials.
Patent Information
- Application Number
- CN202610824080.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-06-09
AI Technical Summary
In the hot pressing process of existing environmentally friendly building materials, phase change materials are prone to melting and leakage, resulting in material waste and reduced interfacial bonding, which affects the mechanical properties of the boards.
Chemical crosslinking of carboxymethylated straw fiber with itaconic acid-epoxy soybean oil copolymer resin, combined with interface modification of dopamine and γ-aminopropyltriethoxysilane, enhances the interfacial bonding between the fiber and resin. In-situ composite of graphene oxide with MIL-101 chromium metal-organic framework enhances the compressive strength of the crystal and confines the phase change material within the pores. Microcrystalline cellulose increases the resin viscosity, and ethylene glycol diglycidyl ether and tertiary amine catalyst form a reversible crosslinking layer to seal the micron-sized pores at the interface. Zinc-aluminum hydrotalcite loaded with nano-silver provides antibacterial properties.
It effectively prevents the leakage of phase change materials during hot pressing and long-term service, maintains the mechanical and antibacterial properties of the sheet, and achieves a long service life for the material.
Smart Images

Figure CN122502139B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of environmentally friendly building materials technology, and more specifically, it relates to an environmentally friendly building material with a long service life and a method for preparing the same. Background Technology
[0002] With the promotion of building energy conservation and green building concepts, the use of biomass waste to prepare environmentally friendly building materials has become an important development direction for the industry. Agricultural waste such as straw and rice husks are widely used to prepare lightweight boards and insulation materials due to their wide availability, renewability, and biodegradability. At the same time, in order to reduce building operating energy consumption, introducing phase change materials into building materials to achieve passive indoor temperature regulation has become an effective means to improve building energy conservation.
[0003] Existing environmentally friendly building materials mostly use biomass fibers and organic phase change materials to be hot-pressed together. However, biomass building boards usually require hot pressing, and the processing temperature is higher than the melting point of most organic phase change materials. During the hot pressing process, the phase change materials melt prematurely and seep out from the matrix, which not only causes material waste and product surface pollution, but also weakens the interfacial bonding force between the fiber and resin, resulting in a decline in the mechanical properties of the board. Summary of the Invention
[0004] To address the problem that existing environmentally friendly building materials not only cause material waste and product surface pollution, but also weaken the interfacial bonding force between fibers and resins, leading to a decline in the mechanical properties of the boards, this application provides an environmentally friendly building material with a long service life and its preparation method.
[0005] This application provides a long-life, environmentally friendly building material and its preparation method, employing the following technical solution: Firstly, this application provides an environmentally friendly building material with a long service life, employing the following technical solution: An environmentally friendly building material with a long service life comprises the following raw materials in parts by weight: 30-40 parts carboxymethylated straw fiber, 20-30 parts fatty acid ester, 15-25 parts MIL-101(Cr)-NH2, 0.1-0.3 parts graphene oxide, 18-25 parts itaconic acid-epoxy soybean oil copolymer resin, 5-10 parts microcrystalline cellulose, 0.5-1.5 parts dopamine, 0.3-0.8 parts γ-aminopropyltriethoxysilane, 1-3 parts ethylene glycol diglycidyl ether, 0.1-0.3 parts tertiary amine catalyst, and 3-8 parts zinc-aluminum hydrotalcite-supported nano-silver.
[0006] By adopting the above technical solution, the carboxyl groups on the surface of carboxymethylated straw fibers undergo a cross-linking reaction with the active groups of itaconic acid epoxidized soybean oil copolymer resin. Combined with the synergistic modification of the fiber interface by dopamine and γ-aminopropyltriethoxysilane, a chemical bonding network between the fiber and the resin matrix is constructed, enhancing the interfacial bonding strength. Graphene oxide and MIL... In-situ composite of 101 chromium metal-organic framework improves the compressive strength of crystals, maintaining the integrity of the pore structure during hot pressing and binding fatty acid esters within the nanopores, reducing melting leakage during high-temperature processing. The thixotropic effect of microcrystalline cellulose increases the viscosity of uncured resin, limiting excessive resin penetration into the framework micropores and preserving the capillary adsorption capacity of the fiber hierarchical porous structure. The reversible cross-linked layer formed by ethylene glycol diglycidyl ether and tertiary amine catalyst at hot pressing temperature seals the interfacial micron-sized pores, further preventing the leakage of molten phase change material. Zinc-aluminum hydrotalcite-loaded nano-silver is uniformly dispersed in the matrix through the coordination and fixation of carboxymethylated fibers, endowing the material with antibacterial properties. Thus, while inhibiting the leakage of phase change material, it maintains the mechanical properties of the board, solving the problem that existing environmentally friendly building materials not only cause material waste and product surface pollution, but also weaken the interfacial bonding force of fiber and resin, leading to a decline in the mechanical properties of the board.
[0007] Preferably, the fatty acid ester is a mixture of methyl palmitate and methyl laurate in a mass ratio of 3.5 to 4.5:1.
[0008] By adopting the above technical solution, the phase transition temperature of fatty acid esters in the range of 3.5 to 4.5:1 is 22 to 26°C, which matches the indoor temperature of the building and can effectively absorb or release latent heat when the room temperature fluctuates. At the same time, the fatty acid esters in this ratio have the best compatibility with the pore size of the metal-organic framework, and the load is stable after vacuum impregnation, reducing the risk of partial liquid leakage caused by deviation of phase transition temperature.
[0009] Preferably, the graphene oxide has a sheet diameter of 0.5–2 μm and an oxidation degree of 40%–50%.
[0010] By adopting the above technical solution, graphene oxide with the specified sheet size and oxidation degree can be uniformly coated on the surface of metal-organic framework crystals, improving the compressive strength of the crystals during hot pressing and preventing the collapse of the pore structure; at the same time, the thermal conductivity of graphene oxide improves the uniformity of the thermal response of the phase change material and reduces leakage caused by local overheating.
[0011] Preferably, the BET specific surface area of the MIL-101(Cr)-NH2 is 2800-3400 m² / g.
[0012] By adopting the above technical solution, the metal-organic framework with a specific surface area has abundant nanoscale pores, which can effectively bind fatty acid ester molecules inside the pores through steric hindrance and capillary effect, reduce the migration and leakage rate of the phase change material during thermal cycling, and maintain a high phase change enthalpy value.
[0013] Preferably, the degree of substitution of the carboxymethylated straw fiber is 0.4 to 0.6, the fiber length is 50 to 200 μm, and the diameter is 5 to 20 μm.
[0014] By adopting the above technical solution, the fiber with this degree of substitution has an appropriate amount of carboxymethyl functional groups, which can form a stable chemical crosslink with the resin matrix and provide coordination fixation sites for zinc aluminum hydrotalcite loaded with nano-silver; the fiber with this length and diameter can construct a uniform hierarchical porous network, taking into account both the mechanical strength of the skeleton and the capillary adsorption capacity.
[0015] Secondly, this application provides a method for preparing a long-lasting environmentally friendly building material, employing the following technical solution: A method for preparing a long-life environmentally friendly building material, applied to the aforementioned long-life environmentally friendly building material, includes the following steps: S1. After dissolving carboxymethylated straw fibers in a DMAc / LiCl solvent system, the fibers are subjected to directional freeze-drying to obtain a carboxymethylated straw fiber skeleton with a hierarchical porous structure. S2. Graphene oxide and MIL-101(Cr)-NH2 are combined in situ via hydrothermal reaction to form GO / MIL-101(Cr)-NH2 composite crystals. Fatty acid esters are then encapsulated in the channels of the GO / MIL-101(Cr)-NH2 composite crystals by vacuum impregnation to obtain GO-enhanced fatty acid ester@MIL-101(Cr)-NH2 composite microspheres. S3. The carboxymethylated straw fiber skeleton was sequentially immersed in a Tris-HCl buffer solution of dopamine, an ethanol solution of γ-aminopropyltriethoxysilane, and an ethanol mixture of ethylene glycol diglycidyl ether and a tertiary amine catalyst for surface modification to obtain the modified skeleton. S4. Mix fatty acid ester@MIL-101(Cr)-NH2 composite microspheres, modified skeleton, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose and zinc aluminum hydrotalcite loaded with silver nanoparticles, and pre-cur at room temperature to obtain a pre-cured board. S5. Immerse the pre-cured board in an ethanol / water mixture for selective dissolution to remove uncrosslinked resin, dry it, and then perform post-curing and cooling to obtain environmentally friendly building materials.
[0016] By adopting the above technical solutions, directional cryogenic pore-forming constructs a fiber-hierarchical porous structure, providing a space for the phase change material composite microspheres and preserving capillary adsorption channels. In-situ composite of graphene oxide enhances the strength of the metal-organic framework crystals. Three-layer interface modification constructs a biomimetic adhesion and reversible cross-linking composite interface layer. Room temperature pre-curing combined with selective dissolution pore-forming preserves the skeletal pores, and post-curing activates the temperature-sensitive sealing layer. The coordinated steps achieve leakage prevention of the phase change material during processing and service, while ensuring the mechanical properties and antibacterial durability of the board.
[0017] Preferably, in step S1, the freezing temperature of the directional freeze drying is -200 to -190°C, the drying temperature is -55 to -45°C, the vacuum degree is ≤10Pa, the drying time is 46 to 50 hours, and the macropore diameter of the hierarchical porous structure is 10 to 50 μm, the mesopore diameter is 2 to 5 μm, and the micropore diameter is ≤2 nm.
[0018] By adopting the above technical solution, the hierarchical porous structure formed by directional freeze drying has a gradient pore size distribution from nanometer to micrometer. The macropores provide a space for the composite microspheres, and the mesopores and micropores adsorb a small amount of leaked phase change material through capillary effect. At the same time, the structure can still retain some porosity after hot pressing, and play a passive leak prevention function.
[0019] Preferably, in step S2, the hydrothermal reaction temperature is 215–225°C and the time is 7–9 hours, the vacuum impregnation temperature is 60–70°C, the vacuum degree is 0.09–0.095 MPa, and the time is 5–7 hours.
[0020] By adopting the above technical solution, the metal-organic framework crystals are fully grown and the graphene oxide is uniformly composited under hydrothermal reaction. The vacuum impregnation parameters ensure that the fatty acid esters fully enter the channels and there are no residues on the surface, thus obtaining composite microspheres with stable loading and good dispersion, providing a uniform phase change material carrier for subsequent mixing and hot pressing.
[0021] Preferably, in step S3, the pH value of the Tris-HCl buffer solution of dopamine is 8.3-8.7, the concentration of dopamine is 1.5-2.5 mg / mL, the mass fraction of the ethanol solution of γ-aminopropyltriethoxysilane is 4.5-5.5%, the mass fraction of the ethanol mixture of ethylene glycol diglycidyl ether and tertiary amine catalyst is 4.5-5.5%, and during the surface modification, the impregnation temperature of dopamine is 22-28°C for 10-14 hours, the grafting temperature of γ-aminopropyltriethoxysilane is 55-65°C for 1.5-2.5 hours, and the loading temperature of ethylene glycol diglycidyl ether and tertiary amine catalyst is 22-28°C for 0.5-1.5 hours.
[0022] By adopting the above technical solution, surface-modified dopamine forms a uniform biomimetic adhesion layer on the fiber surface, γ-aminopropyltriethoxysilane is grafted onto it to introduce active silane groups, ethylene glycol diglycidyl ether and tertiary amine catalyst are uniformly loaded, and the three-layer modification synergistically constructs an interface layer that can reversibly crosslink in response to temperature changes, forming a seal during processing and maintaining air permeability during service, effectively preventing the leakage of phase change material along the interface.
[0023] Preferably, in step S4, the mixing speed is 60-100 rpm for 4-6 minutes, the pre-curing temperature is 23-27°C for 22-26 hours, in step S5, the volume ratio of the ethanol / water mixture is 1:1, the selective dissolution temperature is 28-32°C for 5-7 hours, the drying temperature is 35-45°C, the vacuum degree is 0.08-0.09 MPa for 8-12 hours, the post-curing temperature is 75-85°C for 10-14 hours, and the cooling is natural cooling to room temperature.
[0024] By adopting the above technical solution, the mixing ensures that the components are evenly dispersed and avoids the breakage of the composite microspheres. Room temperature pre-curing allows the resin to reach a partially cross-linked state to maintain the shape of the board while retaining the solubility of the uncross-linked part. Selective dissolution removes the uncross-linked resin that blocks the pores, restores the capillary adsorption capacity of the skeleton, and post-curing activates the temperature-sensitive sealing layer and makes the resin completely cross-linked. Natural cooling causes the sealing layer to partially de-cross-link and achieves the transformation to air permeability, thus achieving a balance between leakage prevention and mechanical properties.
[0025] In summary, this application has the following beneficial effects: 1. Because this application uses carboxymethylated fibers to form chemical crosslinks with resin, and combines dopamine and silane interface modification to enhance the bonding force, graphene oxide to enhance the metal-organic framework crystals, binds fatty acid esters in the channels to reduce hot pressing leakage, microcrystalline cellulose to increase resin viscosity to limit its penetration into micropores, retains the capillary adsorption capacity of the framework, and reversible crosslinking agent to seal the interface pores to prevent leakage, the components work together to suppress the leakage of phase change materials and maintain mechanical properties, thus solving the problems of phase change material leakage and weak interface bonding force in hot pressing.
[0026] 2. This application improves the compressive strength of crystals by in-situ composite of graphene oxide and MIL 101 chromium metal-organic framework, binds fatty acid esters in nanopores, and seals the micron-sized pores at the interface by a reversible cross-linked layer formed by ethylene glycol diglycidyl ether and tertiary amine catalyst at hot-pressing temperature. Combined with the capillary adsorption effect of hierarchical porous fiber skeleton, multiple leakage prevention is achieved, so that the material maintains a low leakage rate after long-term thermal cycling.
[0027] 3. This application constructs a chemical bonding network between the fiber and the resin matrix through chemical crosslinking of carboxymethylated straw fiber and itaconic acid epoxy soybean oil copolymer resin, combined with interface modification of dopamine and γ-aminopropyltriethoxysilane, which enhances the interfacial bonding strength. At the same time, the zinc-aluminum hydrotalcite loaded with nano-silver is uniformly dispersed through the coordination and fixation effect of carboxymethylated fiber, which endows the material with antibacterial properties, so that the material can maintain high flexural strength and low water absorption while inhibiting the leakage of phase change material.
[0028] 4. The preparation method of this application adopts a room temperature curing resin system to avoid high temperature processing leakage. It combines a step-by-step process of directional freezing to create pores, selective dissolution to create pores to retain the skeleton adsorption channels, and post-curing to activate the temperature-sensitive sealing layer. This achieves the control of high temperature sealing and leakage prevention during the processing stage and room temperature air permeability to maintain performance during the service stage. Moreover, the raw materials used are mainly biomass and industrial by-products, which have good environmental friendliness and processability. Attached Figure Description
[0029] Figure 1 This is a flowchart of a method for preparing a long-life, environmentally friendly building material provided in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Technical concept: Existing biomass-based environmentally friendly building materials mostly use biomass fibers and organic phase change materials to be hot-pressed. After the introduction of organic phase change materials, the hot-pressing temperature is higher than the melting point of the phase change materials, which leads to the melting and leakage of the phase change materials and weakens the interfacial bonding between the fiber and the resin. The melting and seepage during the high-temperature processing stage and the slow migration after thermal cycling during long-term service stage make it difficult for a single leak prevention method to deal with the leakage risk at both stages at the same time. In addition, insufficient interfacial bonding will provide a channel for leakage.
[0032] Based on this, this application utilizes in-situ composite graphene oxide to enhance the compressive strength of MIL 101 chromium metal-organic framework crystals, ensuring the integrity of the pores during hot pressing and confining fatty acid esters within the nanopores. A three-layer modification of the fiber surface is performed using dopamine and γ-aminopropyltriethoxysilane, introducing ethylene glycol diglycidyl ether and a tertiary amine catalyst to form a thermosensitive reversible crosslinking layer. This seals the interfacial pores at processing temperatures and maintains permeability at service temperatures. Combining directional cryogenic pore formation and selective dissolution pore formation retains the capillary adsorption capacity of the hierarchical porous framework, achieving passive capture of trace amounts of leaked phase change material. Simultaneously, a room-temperature curing resin system is used to avoid leakage during high-temperature processing, solving the problems of phase change material leakage and weak interfacial bonding during hot pressing.
[0033] Unless otherwise specified, all experimental methods used below are conventional methods. All materials, reagents, methods, and instruments used, unless otherwise specified, are conventional materials, reagents, methods, and instruments in this field, which can be obtained commercially or prepared according to literature methods by those skilled in the art.
[0034] Preparation Example 1: Preparation of Carboxymethylated Straw Fiber 100g of straw fiber was added to 1000mL of 20% sodium hydroxide solution and stirred at 30℃ for 2 hours to alkalize. After filtration, alkalized fiber was obtained. The length of the straw fiber was 50-200μm and the diameter was 5-20μm. The alkalized fiber was added to 1000 mL of isopropanol and 50 g of chloroacetic acid. The reaction was carried out at 60 °C for 3 hours. After the reaction was completed, the pH was adjusted to 7.0 with glacial acetic acid. The mixture was filtered and washed successively with 70% ethanol and 95% ethanol. The mixture was then vacuum dried at 60 °C for 12 hours to obtain carboxymethylated straw fiber.
[0035] Preparation Example 2: Synthesis of MIL-101(Cr)-NH2 Add 4g Cr(NO3)3·9H2O, 1.8g 2-aminoterephthalic acid and 40mL deionized water to a high-pressure reactor lined with polytetrafluoroethylene, add 0.5mL hydrofluoric acid (40wt%), seal and hydrothermally react at 220℃ for 8 hours. After naturally cooling to room temperature, the product was collected by centrifugation, washed three times with deionized water and twice with anhydrous ethanol, and then dried under vacuum at 150°C for 12 hours to obtain MIL-101(Cr)-NH2 crystals.
[0036] Preparation Example 3: Preparation of Itaconic Acid-Epoxy Soybean Oil Copolymer Resin Add itaconic acid and epoxidized soybean oil to a 500mL three-necked flask equipped with a stirrer, nitrogen inlet and reflux condenser, in a molar ratio of 1.2:1. Then, p-toluenesulfonic acid was added as a catalyst at a rate of 1.0% of the total mass of the reactants, and nitrogen gas was introduced. The mixture was heated in an oil bath to 120°C, stirred at 250 rpm, and reacted for 4 hours. After the reaction was completed, it was naturally cooled to 60°C to obtain the itaconic acid-epoxy soybean oil copolymer prepolymer. Take the itaconic acid-epoxidized soybean oil copolymer prepolymer, add microcrystalline cellulose at a mass ratio of 3:1 of prepolymer to microcrystalline cellulose, and stir at 900 rpm for 15 minutes at room temperature to obtain itaconic acid-epoxidized soybean oil copolymer resin.
[0037] Preparation Example 4: Preparation of Silver Nanoparticles Supported by Zinc Aluminum Layered Double Hydroxide Dissolve 0.1 mol Zn(NO3)2·6H2O and 0.05 mol Al(NO3)3·9H2O in 100 mL of deionized water to prepare a mixed salt solution; Dissolve 0.3 mol of urea in 100 mL of deionized water to prepare a precipitant solution; The mixed salt solution was slowly added dropwise to the precipitant solution under vigorous stirring. After the addition was complete, the solution was transferred to a hydrothermal reactor and reacted at 120°C for 12 hours. Then, it was centrifuged, washed with deionized water until neutral, and dried at 60°C to obtain ZnAl hydrotalcite. 1 g of ZnAl hydrotalcite was dispersed in 50 mL of deionized water, 0.01 g of AgNO3 was added, and the mixture was stirred for 2 hours in the dark. Then, 0.02 g of sodium citrate was added as a reducing agent, and the mixture was stirred for another hour. The mixture was then centrifuged, washed with deionized water, and dried under vacuum at 40 °C to obtain zinc-aluminum hydrotalcite-supported silver nanoparticles.
[0038] To better understand the above technical solutions, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments.
[0039] Please see the appendix Figure 1 The following is a further description with reference to the embodiments: Example 1: A long-life environmentally friendly building material, comprising the following raw materials in parts by weight: 35 parts carboxymethylated straw fiber, 25 parts fatty acid ester, 20 parts MIL-101(Cr)-NH2, 0.2 parts graphene oxide, 21.5 parts itaconic acid-epoxy soybean oil copolymer resin, 7.5 parts microcrystalline cellulose, 1 part dopamine, 0.55 parts γ-aminopropyltriethoxysilane, 2 parts ethylene glycol diglycidyl ether, 0.2 parts tertiary amine catalyst, and 5.5 parts zinc-aluminum hydrotalcite-supported nano-silver.
[0040] The fatty acid ester is a mixture of methyl palmitate and methyl laurate in a mass ratio of 4:1.
[0041] The graphene oxide sheet has a diameter of 1.25 μm and an oxidation degree of 45%.
[0042] The BET specific surface area of MIL-101(Cr)-NH2 is 3100 m² / g.
[0043] The degree of substitution of carboxymethylated straw fiber is 0.5, the fiber length is 125 μm, and the diameter is 12.5 μm.
[0044] A method for preparing a long-life environmentally friendly building material, applied to the aforementioned long-life environmentally friendly building material, includes the following steps: S1. After dissolving carboxymethylated straw fibers in a DMAc / LiCl solvent system, the fibers are subjected to directional freeze-drying to obtain a carboxymethylated straw fiber skeleton with a hierarchical porous structure. The directional freeze-drying process involves a freezing temperature of -195℃, a drying temperature of -50℃, a vacuum degree of ≤10Pa, a drying time of 48 hours, and a hierarchical porous structure with macropores of 30μm, mesopores of 3.5μm, and micropores of ≤2nm.
[0045] S2. Graphene oxide and MIL-101(Cr)-NH2 are combined in situ via hydrothermal reaction to form GO / MIL-101(Cr)-NH2 composite crystals. Fatty acid esters are then encapsulated in the channels of the GO / MIL-101(Cr)-NH2 composite crystals by vacuum impregnation to obtain GO-enhanced fatty acid ester@MIL-101(Cr)-NH2 composite microspheres. The hydrothermal reaction was carried out at a temperature of 220℃ for 8 hours, while the vacuum impregnation was carried out at a temperature of 65℃, a vacuum of 0.0925 MPa for 6 hours.
[0046] S3. The carboxymethylated straw fiber skeleton was sequentially immersed in a Tris-HCl buffer solution of dopamine, an ethanol solution of γ-aminopropyltriethoxysilane, and an ethanol mixture of ethylene glycol diglycidyl ether and a tertiary amine catalyst for surface modification to obtain the modified skeleton. The pH value of the Tris-HCl buffer solution for dopamine was 8.5, the concentration of dopamine was 2 mg / mL, the mass fraction of the ethanol solution of γ-aminopropyltriethoxysilane was 5%, the mass fraction of the ethanol mixture of ethylene glycol diglycidyl ether and tertiary amine catalyst was 5%, and during surface modification, the impregnation temperature of dopamine was 25℃ and the time was 12 hours, the grafting temperature of γ-aminopropyltriethoxysilane was 60℃ and the time was 2 hours, and the loading temperature of ethylene glycol diglycidyl ether and tertiary amine catalyst was 25℃ and the time was 1 hour.
[0047] S4. Mix fatty acid ester@MIL-101(Cr)-NH2 composite microspheres, modified skeleton, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose and zinc aluminum hydrotalcite loaded with silver nanoparticles, and pre-cur at room temperature to obtain a pre-cured board. The mixing speed was 80 rpm, the time was 5 minutes, the pre-curing temperature was 25℃, and the time was 24 hours.
[0048] S5. Immerse the pre-cured board in an ethanol / water mixture for selective dissolution to remove uncrosslinked resin, dry it, and then perform post-curing and cooling to obtain environmentally friendly building materials.
[0049] The volume ratio of the ethanol / water mixture was 1:1. The selective dissolution temperature was 30℃ and the time was 6 hours. The drying temperature was 40℃, the vacuum degree was 0.085MPa and the time was 10 hours. The post-curing temperature was 80℃ and the time was 12 hours. The cooling was natural cooling to room temperature.
[0050] Example 2: This example differs from Example 1 above in that: An environmentally friendly building material with a long service life comprises the following raw materials in parts by weight: 30 parts carboxymethylated straw fiber, 20 parts fatty acid ester, 15 parts MIL-101(Cr)-NH2, 0.1 parts graphene oxide, 18 parts itaconic acid-epoxy soybean oil copolymer resin, 5 parts microcrystalline cellulose, 0.5 parts dopamine, 0.3 parts γ-aminopropyltriethoxysilane, 1 part ethylene glycol diglycidyl ether, 0.1 parts tertiary amine catalyst, and 3 parts zinc-aluminum hydrotalcite-supported nano-silver.
[0051] The fatty acid ester is a mixture of methyl palmitate and methyl laurate in a mass ratio of 3.5:1.
[0052] The graphene oxide sheet has a diameter of 0.5 μm and an oxidation degree of 40%.
[0053] The BET specific surface area of MIL-101(Cr)-NH2 is 2800 m² / g.
[0054] The degree of substitution of carboxymethylated straw fiber is 0.4, the fiber length is 50 μm, and the diameter is 5 μm.
[0055] A method for preparing a long-life environmentally friendly building material, applied to the aforementioned long-life environmentally friendly building material, includes the following steps: S1. After dissolving carboxymethylated straw fibers in a DMAc / LiCl solvent system, the fibers are subjected to directional freeze-drying to obtain a carboxymethylated straw fiber skeleton with a hierarchical porous structure. The directional freeze-drying process involves a freezing temperature of -190℃, a drying temperature of -45℃, a vacuum degree of ≤10Pa, a drying time of 46 hours, and a hierarchical porous structure with macropores of 10μm, mesopores of 2μm, and micropores of ≤2nm.
[0056] S2. Graphene oxide and MIL-101(Cr)-NH2 are combined in situ via hydrothermal reaction to form GO / MIL-101(Cr)-NH2 composite crystals. Fatty acid esters are then encapsulated in the channels of the GO / MIL-101(Cr)-NH2 composite crystals by vacuum impregnation to obtain GO-enhanced fatty acid ester@MIL-101(Cr)-NH2 composite microspheres. The hydrothermal reaction was carried out at a temperature of 215℃ for 7 hours, while the vacuum impregnation process was carried out at a temperature of 60℃, a vacuum degree of 0.09 MPa, and a time of 5 hours.
[0057] S3. The carboxymethylated straw fiber skeleton was sequentially immersed in a Tris-HCl buffer solution of dopamine, an ethanol solution of γ-aminopropyltriethoxysilane, and an ethanol mixture of ethylene glycol diglycidyl ether and a tertiary amine catalyst for surface modification to obtain the modified skeleton. The dopamine Tris-HCl buffer solution had a pH of 8.3 and a dopamine concentration of 1.5 mg / mL. The ethanol solution of γ-aminopropyltriethoxysilane had a mass fraction of 4.5%, and the ethanol mixture of ethylene glycol diglycidyl ether and tertiary amine catalyst had a mass fraction of 4.5%. During surface modification, the dopamine impregnation temperature was 22℃ for 10 hours, the γ-aminopropyltriethoxysilane grafting temperature was 55℃ for 1.5 hours, and the ethylene glycol diglycidyl ether and tertiary amine catalyst loading temperature was 22℃ for 0.5 hours.
[0058] S4. Mix fatty acid ester@MIL-101(Cr)-NH2 composite microspheres, modified skeleton, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose and zinc aluminum hydrotalcite loaded with silver nanoparticles, and pre-cur at room temperature to obtain a pre-cured board. The mixing speed was 60 rpm, the time was 4 minutes, the pre-curing temperature was 23℃, and the time was 22 hours.
[0059] S5. Immerse the pre-cured board in an ethanol / water mixture for selective dissolution to remove uncrosslinked resin, dry it, and then perform post-curing and cooling to obtain environmentally friendly building materials.
[0060] The volume ratio of the ethanol / water mixture was 1:1. The selective dissolution temperature was 28℃ and the time was 5 hours. The drying temperature was 35℃, the vacuum degree was 0.08MPa and the time was 8 hours. The post-curing temperature was 75℃ and the time was 10 hours. The cooling was natural cooling to room temperature.
[0061] Example 3: This example differs from Example 1 above in that: An environmentally friendly building material with a long service life comprises the following raw materials in parts by weight: 40 parts carboxymethylated straw fiber, 30 parts fatty acid ester, 25 parts MIL-101(Cr)-NH2, 0.3 parts graphene oxide, 25 parts itaconic acid-epoxy soybean oil copolymer resin, 10 parts microcrystalline cellulose, 1.5 parts dopamine, 0.8 parts γ-aminopropyltriethoxysilane, 3 parts ethylene glycol diglycidyl ether, 0.3 parts tertiary amine catalyst, and 8 parts zinc-aluminum hydrotalcite-supported nano-silver.
[0062] The fatty acid ester is a mixture of methyl palmitate and methyl laurate in a mass ratio of 4.5:1.
[0063] The graphene oxide sheet has a diameter of 2 μm and an oxidation degree of 50%.
[0064] The BET specific surface area of MIL-101(Cr)-NH2 is 3400 m² / g.
[0065] The degree of substitution of carboxymethylated straw fiber is 0.6, the fiber length is 200 μm, and the diameter is 20 μm.
[0066] A method for preparing a long-life environmentally friendly building material, applied to the aforementioned long-life environmentally friendly building material, includes the following steps: S1. After dissolving carboxymethylated straw fibers in a DMAc / LiCl solvent system, the fibers are subjected to directional freeze-drying to obtain a carboxymethylated straw fiber skeleton with a hierarchical porous structure. The directional freeze-drying process involves a freezing temperature of -200℃, a drying temperature of -55℃, a vacuum degree of ≤10Pa, a drying time of 50 hours, and a hierarchical porous structure with macropores of 50μm, mesopores of 5μm, and micropores of ≤2nm.
[0067] S2. Graphene oxide and MIL-101(Cr)-NH2 are combined in situ via hydrothermal reaction to form GO / MIL-101(Cr)-NH2 composite crystals. Fatty acid esters are then encapsulated in the channels of the GO / MIL-101(Cr)-NH2 composite crystals by vacuum impregnation to obtain GO-enhanced fatty acid ester@MIL-101(Cr)-NH2 composite microspheres. The hydrothermal reaction was carried out at a temperature of 225℃ for 9 hours, while the vacuum impregnation was carried out at a temperature of 70℃, a vacuum degree of 0.095MPa, and a time of 7 hours.
[0068] S3. The carboxymethylated straw fiber skeleton was sequentially immersed in a Tris-HCl buffer solution of dopamine, an ethanol solution of γ-aminopropyltriethoxysilane, and an ethanol mixture of ethylene glycol diglycidyl ether and a tertiary amine catalyst for surface modification to obtain the modified skeleton. The dopamine Tris-HCl buffer solution had a pH of 8.7 and a dopamine concentration of 2.5 mg / mL. The ethanol solution of γ-aminopropyltriethoxysilane had a mass fraction of 5.5%, and the ethanol mixture of ethylene glycol diglycidyl ether and tertiary amine catalyst had a mass fraction of 5.5%. During surface modification, the dopamine impregnation temperature was 28℃ for 14 hours, the γ-aminopropyltriethoxysilane grafting temperature was 65℃ for 2.5 hours, and the ethylene glycol diglycidyl ether and tertiary amine catalyst loading temperature was 28℃ for 1.5 hours.
[0069] S4. Mix fatty acid ester@MIL-101(Cr)-NH2 composite microspheres, modified skeleton, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose and zinc aluminum hydrotalcite loaded with silver nanoparticles, and pre-cur at room temperature to obtain a pre-cured board. The mixing speed was 100 rpm, the time was 6 minutes, the pre-curing temperature was 27℃, and the time was 26 hours.
[0070] S5. Immerse the pre-cured board in an ethanol / water mixture for selective dissolution to remove uncrosslinked resin, dry it, and then perform post-curing and cooling to obtain environmentally friendly building materials.
[0071] The volume ratio of the ethanol / water mixture was 1:1. The selective dissolution temperature was 32℃ and the time was 7 hours. The drying temperature was 45℃, the vacuum degree was 0.09MPa and the time was 12 hours. The post-curing temperature was 85℃ and the time was 14 hours. The cooling was natural cooling to room temperature.
[0072] Comparative Example 1: A straw fiber building material board, prepared by the following method: Natural straw fibers are crushed to a length of 100-200μm and mixed with urea-formaldehyde resin at a mass ratio of 70:30. 1% of ammonium chloride curing agent by weight of the resin is added, and the mixture is stirred evenly before being laid in a mold. The mixture is then hot-pressed at 120℃ and 3MPa for 10 minutes. After cooling, straw fiber building material boards are obtained.
[0073] Comparative Example 2: This comparative example differs from Example 1 above in that: Graphene oxide-free, meaning no graphene oxide is added in step S2, otherwise the same as in Example 1.
[0074] Comparative Example 3: This comparative example differs from Example 1 above in that: The catalyst is without ethylene glycol diglycidyl ether and tertiary amine catalyst, that is, the loading modification of ethylene glycol diglycidyl ether and tertiary amine catalyst is not carried out in step S3, and the rest is the same as in Example 1.
[0075] Comparative Example 4: This comparative example differs from Example 1 above in that: In step S5, there is no selective dissolution to create pores. That is, in step S5, the pre-cured board is not immersed in the ethanol / water mixture, but is directly dried and post-cured. The rest is the same as in Example 1.
[0076] Comparative Example 5: This comparative example differs from Example 1 above in that: The fatty acid ester was a mixture of methyl palmitate and methyl laurate in a mass ratio of 2:1, and the rest was the same as in Example 1.
[0077] Comparative Example 6: This comparative example differs from Example 1 above in that: The itaconic acid-epoxy soybean oil copolymer resin was replaced with urea-formaldehyde resin, and the curing method was changed from room temperature curing to hot pressing at 120°C for 10 minutes. The rest was the same as in Example 1.
[0078] Comparative Example 7: This comparative example differs from Example 1 above in that: The degree of substitution of carboxymethylated straw fiber was 0.2, and the rest was the same as in Example 1.
[0079] Performance testing: Leakage rate of phase change material: Place a 20mm×20mm×10mm sample in an aluminum foil weighing bottle and cycle it alternately between 0℃ and 40℃, maintaining each temperature for 30 minutes. The heating / cooling rate is 1℃ / min. Weigh the sample after every 50 cycles and calculate the mass loss rate as the leakage rate. Repeat the cycle 200 times and record the total leakage rate after 200 cycles. Bending strength: Refer to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and decorative wood-based panels", three-point bending method, span 150mm, loading speed 5mm / min; 24h water absorption rate: Referring to GB / T 17657-2013, immerse a 50mm×50mm sample in distilled water at 23℃ for 24 hours, weigh it and calculate the water absorption rate; Antibacterial properties: Refer to GB / T 21866-2008, film application method, strain is Aspergillus niger, incubation time is 28 days, observe and record the mold grade, grade 0 is no mold, grade 1 is mold area ≤10%, grade 2 is mold area 11%~25%, grade 3 is mold area 26%~50%, grade 4 is mold area ≥51%; The test results are shown in Table 1.
[0080] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-7
[0081] As can be seen from Examples 1 to 3 and Comparative Examples 1 to 7, and Table 1, an environmentally friendly building material with low phase change material leakage rate, high flexural strength, low water absorption rate and excellent antibacterial properties was obtained through the synergistic combination of carboxymethylated straw fiber, fatty acid ester, MIL-101 chromium metal-organic framework, graphene oxide, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose, dopamine, γ-aminopropyltriethoxysilane, ethylene glycol diglycidyl ether, tertiary amine catalyst and zinc aluminum hydrotalcite supported on silver nanoparticles.
[0082] As can be seen from Example 1 and Comparative Example 1, and Table 1, the room-temperature curing crosslinking network of carboxymethylated straw fiber and itaconic acid-epoxy soybean oil copolymer resin, combined with the interface modification of dopamine and γ-aminopropyltriethoxysilane, enhances the bonding strength between the fiber and the resin matrix, thereby improving the bending performance of the material. At the same time, the synergistic effect of the hierarchical porous structure and the hydrophobic modification layer reduces the water absorption rate of the material. The coordination antibacterial mechanism of zinc-aluminum hydrotalcite-loaded nano-silver and carboxymethylated fiber inhibits the growth of Aspergillus niger, giving the material good antibacterial durability.
[0083] As can be seen from Example 1 and Comparative Example 2, and Table 1, the addition of graphene oxide can enhance the compressive strength of the MIL-101 chromium metal-organic framework crystal, enabling it to maintain the integrity of the pore structure during hot pressing, thereby effectively confining the fatty acid ester phase change material and reducing leakage during thermal cycling. At the same time, the high thermal conductivity of graphene oxide is beneficial to the uniformity of the thermal response of the phase change material, avoiding the aggravation of leakage caused by local overheating.
[0084] As can be seen from Example 1 and Comparative Example 3, and Table 1, the thermosensitive reversible crosslinking layer formed by ethylene glycol diglycidyl ether and tertiary amine catalyst at the processing temperature can seal the micron-sized pores at the fiber-resin interface, thereby preventing leakage of molten fatty acid esters during the post-curing stage; at the service temperature, the crosslinking layer partially decrosslinks, restoring the permeability of the material and avoiding the impact of complete sealing on the heat absorption and release efficiency of the phase change material.
[0085] Combining Example 1 and Comparative Example 4 with Table 1, it can be seen that selective dissolution pore-forming can remove the uncrosslinked resin that has penetrated into the pores of the skeleton during the pre-curing stage, and re-expose the hierarchical porous structure of the carboxymethylated straw fiber. This allows the porous skeleton to adsorb trace amounts of leaked phase change material through capillary effect during service, thus achieving a passive leak prevention function.
[0086] As can be seen from Example 1 and Comparative Example 6 and Table 1, using itaconic acid-epoxy soybean oil copolymer resin and curing at room temperature can avoid the large-scale melting and leakage of fatty acid esters caused by high-temperature hot pressing. However, when using traditional urea-formaldehyde resin and hot pressing at high temperature, the phase change material will leak severely during the curing process, resulting in an increased leakage rate of the product and a decrease in mechanical properties and water resistance.
[0087] As can be seen from Example 1 and Comparative Example 7, and Table 1, when the degree of substitution of carboxymethylated straw fiber is between 0.4 and 0.6, the fiber has moderate hydrophilicity and reactivity, and can form a strong interfacial bond with the resin matrix. At the same time, it provides effective coordination sites for metal ions, thereby obtaining a low leakage rate and good mechanical properties. When the degree of substitution is too low, the fiber reactivity is insufficient, the interfacial bonding force is weakened, resulting in an increased leakage rate and a decrease in mechanical properties.
[0088] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A long-life, environmentally friendly building material, characterized in that, The raw materials include the following parts by weight: 30-40 parts carboxymethylated straw fiber, 20-30 parts fatty acid ester, 15-25 parts MIL-101(Cr)-NH2, 0.1-0.3 parts graphene oxide, 18-25 parts itaconic acid-epoxidized soybean oil copolymer resin, 5-10 parts microcrystalline cellulose, 0.5-1.5 parts dopamine, 0.3-0.8 parts γ-aminopropyltriethoxysilane, 1-3 parts ethylene glycol diglycidyl ether, 0.1-0.3 parts tertiary amine catalyst, and 3-8 parts zinc-aluminum hydrotalcite-supported nano-silver. The fatty acid ester is a mixture of methyl palmitate and methyl laurate in a mass ratio of 3.5 to 4.5:1; The preparation method of the environmentally friendly building material includes the following steps: S1. After dissolving carboxymethylated straw fibers in a DMAc / LiCl solvent system, the fibers are subjected to directional freeze-drying to obtain a carboxymethylated straw fiber skeleton with a hierarchical porous structure. S2. Graphene oxide and MIL-101(Cr)-NH2 are combined in situ via hydrothermal reaction to form GO / MIL-101(Cr)-NH2 composite crystals. Fatty acid esters are then encapsulated in the channels of the GO / MIL-101(Cr)-NH2 composite crystals by vacuum impregnation to obtain GO-enhanced fatty acid ester@MIL-101(Cr)-NH2 composite microspheres. S3. The carboxymethylated straw fiber skeleton was sequentially immersed in a Tris-HCl buffer solution of dopamine, an ethanol solution of γ-aminopropyltriethoxysilane, and an ethanol mixture of ethylene glycol diglycidyl ether and a tertiary amine catalyst for surface modification to obtain the modified skeleton. S4. Mix fatty acid ester@MIL-101(Cr)-NH2 composite microspheres, modified skeleton, itaconic acid-epoxy soybean oil copolymer resin, microcrystalline cellulose and zinc aluminum hydrotalcite loaded with silver nanoparticles, and pre-cur at room temperature to obtain a pre-cured board. S5. Immerse the pre-cured board in an ethanol / water mixture for selective dissolution to remove uncrosslinked resin, dry it, and then perform post-curing and cooling to obtain environmentally friendly building materials. In step S1, the freezing temperature of the directional freeze drying is -200 to -190°C, the drying temperature is -55 to -45°C, the vacuum degree is ≤10Pa, and the drying time is 46 to 50 hours. The macropore diameter of the hierarchical porous structure is 10 to 50 μm, the mesopore diameter is 2 to 5 μm, and the micropore diameter is ≤2 nm.
2. The environmentally friendly building material with a long service life according to claim 1, characterized in that: The graphene oxide has a sheet diameter of 0.5–2 μm and an oxidation degree of 40%–50%.
3. The environmentally friendly building material with a long service life according to claim 1, characterized in that: The BET specific surface area of the MIL-101(Cr)-NH2 is 2800-3400 m² / g.
4. The environmentally friendly building material with a long service life according to claim 1, characterized in that: The carboxymethylated straw fiber has a degree of substitution of 0.4 to 0.6, a fiber length of 50 to 200 μm, and a diameter of 5 to 20 μm.
5. The method for preparing a long-service-life environmentally friendly building material according to claim 1, characterized in that: In step S2, the hydrothermal reaction is carried out at a temperature of 215–225°C for 7–9 hours, and the vacuum impregnation is carried out at a temperature of 60–70°C for 0.09–0.095 MPa for 5–7 hours.
6. The method for preparing a long-service-life environmentally friendly building material according to claim 1, characterized in that: In step S3, the pH of the Tris-HCl buffer solution of dopamine is 8.3-8.7, the concentration of dopamine is 1.5-2.5 mg / mL, the mass fraction of the ethanol solution of γ-aminopropyltriethoxysilane is 4.5-5.5%, the mass fraction of the ethanol mixture of ethylene glycol diglycidyl ether and tertiary amine catalyst is 4.5-5.5%, and during the surface modification, the impregnation temperature of dopamine is 22-28°C for 10-14 hours, the grafting temperature of γ-aminopropyltriethoxysilane is 55-65°C for 1.5-2.5 hours, and the loading temperature of ethylene glycol diglycidyl ether and tertiary amine catalyst is 22-28°C for 0.5-1.5 hours.
7. The method for preparing a long-service-life environmentally friendly building material according to claim 1, characterized in that: In step S4, the mixing speed is 60-100 rpm for 4-6 minutes, the pre-curing temperature is 23-27°C for 22-26 hours, and the volume ratio of the ethanol / water mixture is 1:
1. The selective dissolution temperature is 28-32°C for 5-7 hours, the drying temperature is 35-45°C, the vacuum degree is 0.08-0.09 MPa for 8-12 hours, the post-curing temperature is 75-85°C for 10-14 hours, and the cooling is natural cooling to room temperature.
Citation Information
Patent Citations
Nano modified epoxy building thermal insulation material and preparation method thereof
CN119430815A
Efficient and energy-saving building thermal insulation material and preparation method thereof
CN121573928A
